Bactericidal activity of fish galectin 4 derived membrane-binding peptide tagged with oligotryptophan. (June 2017) - Arasu, Abirami; Kumaresan, Venkatesh; Ganesh, Munuswamy-Ramanujam; Pasupuleti, Mukesh; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Arockiaraj, Jesu
Abstract: Galectins belong to the family of galactoside-binding proteins which act as pathogen recognition receptors by recognizing and binding to the carbohydrate present in the bacterial membranes. In this study, a Galectin-4 sequence was identified from the constructed cDNA library of Channa striatus and its structural features were reported. Gene expression analysis revealed that Cs Gal4 was highly expressed in liver and strongly induced by Epizootic Ulcerative Syndrome (EUS) causing pathogens such as Aphanomyces invadans, Aeromonas hydrophila and a viral analogue, poly I:C. To understand the antimicrobial role of putative dimerization site of Cs Gal4, the region was chemically synthesized and its bactericidal effect was determined. G4 peptide exhibited a weak bactericidal activity against Vibrio harveyi, an important aquaculture pathogen. We have also determined the bactericidal activity of the dimerization site by tagging pentamer oligotryptophan (W5) at the C -terminal of G4 peptide. Flow cytometry analysis revealed that G4W induced drastic reduction in cell counts than G4. Electron microscopic images showed membrane blebbings in V. harveyi which indicated the membrane disrupting activity of G4W. Interestingly, both the peptides did not exhibit any hemolytic activity and cytotoxicity towards peripheral blood cells of Channa striatus and the activity was specific only towards the bacterial membrane. Our results suggested that addition of W5 at the C -terminal of membrane-binding peptide remarkably improved its membrane disrupting activity. Highlights: First Galectin-4 cDNA identified and characterized from Channa striatus. Expression of Cs Gal4 up-regulated during fungal and bacterial infection. A putative antimicrobial peptide region (G4) identified from Cs Gal4. Bactericidal property of G4 was improved by tagging oligotryptophan at C -terminal. The activity of the improved peptide was determined as membrane disruption.